How CGIAR interventions can enable policies and institutional mechanisms for gender-equitable food, land and water systems - Joshi, Deepa; Beniwal, Ezaboo; Zaremba, Haley; Myers, Emily; Tsige, Meseret; Adomaa, Faustina Obeng; Koirala, Sanju (CGIAR System Organization, 2025)
Agrifood systems are at the heart of climate crises (CGIAR System Organization 2021). On the one hand, climate crises are leading to unprecedented pressures on food, land and water (FLW) systems, which impact a growing world population, estimated to reach 9-10 billion by 2050. On the other hand, unsustainable agriculture is also a key driver of climate change. In response to this polycrisis, the CGIAR 2030 Research and Innovation Strategy (CGIAR System Organization 2021) calls for a systemic transformation of FLW systems, including changes to policies, institutions and mechanisms. The CGIAR is committed to being a “champion of change” in leveraging science and innovation for a “radical realignment” of FLW systems. Drawing on the significant complementarity between gender transformative approaches and transformative policy and institutional change processes, the focus of this brief is to demonstrate how gender equality and social inclusion (GESI) principles can provide a framework for transforming FLW systems. In this context, this brief contributes to the CGIAR agenda of a radical realignment of FLW systems by introducing scientific, transdisciplinary methods designed to tackle gender inequality and social exclusion.